Estimativa da evapotranspiração espacial em uma região semiárida utilizando sensoriamento remoto - Bezerra, Hélio Nogueira (2013)
With the need to deploy management and monitoring systems of natural resources in areas susceptible to environmental degradation, as is the case of semiarid regions, several works have been developed in order to find effective models and technically and economically viable. Therefore, this study aimed to estimate the daily actual evapotranspiration (ETr) through the application of the Surface Energy Balance Algorithm for Land (SEBAL), from remote sensing products, in a semiarid region, Seridó of the Rio Grande do Norte, and do the validation of these estimates using ETr values obtained by the Penman-Monteith (standard method of the Food and Agriculture Organization-FAO). The SEBAL is based on energy balance method, which allows obtaining the vertical latent heat flux (LE) with orbital images and, consequently, of the evapotranspiration through the difference of flows, also vertical, of heat in the soil (G), sensitive heat (H) and radiation balance (Rn). The study area includes the surrounding areas of the Dourado reservoir, located in the Currais Novos/RN city. For the implementation of the algorithm were used five images TM/Landsat-5. The work was divided in three chapters in order to facilitate a better discussion of each part of the SEBAL processing, distributed as follows: first chapter addressing the spatio-temporal variability of the biophysical variables; second chapter dealing with spatio-temporal distribution of instant and daily radiation balance; and the third chapter discussing the heart of the work, the daily actual evapotranspiration estimation and the validation than to the study area